2014
DOI: 10.1111/jpy.12180
|View full text |Cite
|
Sign up to set email alerts
|

Detection of flavonoids in microalgae from different evolutionary lineages

Abstract: Flavonoids are important secondary plant metabolites believed to be present mainly in land plants. As phenolics were detected previously in microalgae using photometric assays, we wanted to investigate the nature of these phenolics and verify whether flavonoids are present. Therefore, in this study, we used state-of-the-art ultra-high performance liquid chromatography-two-dimensional mass spectrometry (UHPLC-MS/MS) technology to investigate whether microalgae also contain flavonoids. For this, representative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 45 publications
2
110
0
Order By: Relevance
“…82 The biosynthesis of flavonoids proceeds through the phenylpropanoid metabolic pathway, whereas the amino acid phenylalanine acts as the precursor in producing 4-coumaroyl-CoA that combines with malonyl-CoA yielding chalcones. 81,83 The stereospecific cyclization of chalcones results in the formation of the general ring structure of flavonoids. 84 Flavonoids are well known for their superoxide and hydroxyl radical scavenging activities both in hydrophilic and lipophilic systems.…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…82 The biosynthesis of flavonoids proceeds through the phenylpropanoid metabolic pathway, whereas the amino acid phenylalanine acts as the precursor in producing 4-coumaroyl-CoA that combines with malonyl-CoA yielding chalcones. 81,83 The stereospecific cyclization of chalcones results in the formation of the general ring structure of flavonoids. 84 Flavonoids are well known for their superoxide and hydroxyl radical scavenging activities both in hydrophilic and lipophilic systems.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…80 Flavonoids are found to be present mainly in land plants, but recent investigations indicate the presence of flavonoids in marine flora. 81 Several flavonol glycosides, including quercetin derivatives, have been identified in the fresh water microalga Hematococcus pluvialis. 81 Flavonol glycosides are compounds where a sugar molecule is bound with the flavonoid group through a glycosidic bond.…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenolic compounds biosynthesized by Chlorella and Spirulina microalgae were compared [42]. They found that Chlorella microalgae have more content of phoroglucinol, which is used by the pharmaceutical industry -gastrointestinal disorders [43] and also apigenin, which induces autophagy in leukemia cells (Table 2) [44].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…In streptophyte algae, several homologs, but few orthologs of the genes required for flavonoid biosynthesis were detected [121]. That being said, Goiris et al [154] reported the presence of flavonoids in algae from various lineages, including chlorophytes. A 1969 study by Markham and Porter [155] reported on the presence of flavonoids in the charophyceae Nitella , highlighting the need to further investigate streptophyte algae with regard to the presence of these metabolites.…”
Section: Phenylpropanoids and Their Derivatives In Streptophyte Defenmentioning
confidence: 99%